CONTEMPORARY MANAGEMENT OF VENOUS THROMBOEMBOLISM: CLINICAL RISK STRATIFICATION, THROMBOPROPHYLAXIS, AND ANTICOAGULATION WITH ORAL ANTICOAGULANTS - Marques, Mirella Cristina Mazuqueli; Marques, Lucileia Mazuqueli; Medeiros, Rodolfo de Oliveira; Pulvirenti, Dianah Dantas; Carvalho, Fabiana Campos Castro de; Vicenconi, Arthur Menegucci; Bolsoni, Ana Carolina Fontana; Garcia, José Gabriel Cavalcanti; Peixoto, Maria Júlia Daniel; Silva, Edna Pereira da; et al. (Periódicos Brasil. Pesquisa Científica, 2026)
Venous thromboembolism (VTE), encompassing deep vein thrombosis and pulmonary embolism, remains a major global health concern due to its high morbidity and mortality. Over the past decades, significant advances in the understanding of its pathophysiology and management have led to a shift from standardized therapeutic approaches to more individualized strategies. This narrative review aims to analyze contemporary VTE management, focusing on clinical risk stratification, thromboprophylaxis, and the use of direct oral anticoagulants (DOACs). A narrative literature review was conducted using PubMed/MEDLINE, Scopus, Web of Science, and ScienceDirect, including studies published between 2015 and 2026. Clinical trials, systematic reviews, and international guidelines were analyzed to synthesize current evidence. Findings highlight the central role of risk stratification tools, such as the Pulmonary Embolism Severity Index (PESI), in guiding clinical decisions, including outpatient management for low-risk patients. Thromboprophylaxis strategies have evolved with the implementation of validated risk assessment models, particularly in hospitalized populations. The introduction of DOACs represents a major advancement, offering comparable or superior efficacy to vitamin K antagonists, with improved safety profiles and greater convenience. However, their use requires careful consideration in specific populations, including patients with renal impairment, cancer, or pregnancy. Overall, contemporary VTE management reflects a paradigm shift toward personalized medicine, integrating clinical assessment, evidence-based protocols, and patient-centered decision-making. Despite these advances, challenges remain in guideline implementation and treatment individualization. Future research should focus on optimizing long-term outcomes and refining risk stratification models to further enhance clinical care.